Comparison of the effect of propolis and Gluma desensitizer on the management of dentin hypersensitivity: a randomized controlled trial - Shah, Marina; Ahmed Jat, Shahbaz; Aziz, Munazza (Journal of the Pakistan Medical Association, 2024)
Objective: To compare the effect of propolis and gluma desensitisers on the management of dentin hypersensitivity. Method: The single-blind, randomised controlled trial was conducted at the Department of Operative Dentistry, Dr Ishrat ul Ebad Khan Institute of Oral Health Sciences, Dow University of Health Sciences, Karachi, from October 2020 to September 2021, and comprised patients with dentin hypersensitivity who had pain scores of at least 2 on the visual analogue scale. The teeth were randomised into propolis group A and Gluma group B. Baseline pain scores were assessed using visual analogue scale and Schiff's sensitivity scores and compared with scores immediately after the intervention, and then after one week and one month of the intervention. Data was analysed using SPSS 23. Results: Of the 22 patients, 12(54.5%) were females and 10(45.4%) were males. Of the 80 teeth, there were 40(50%) in each of the 2 groups. Significant reduction was observed in dentin hypersensitivity immediately after the application of the desensitising agents (p<0.05). However, after one month, Gluma was more effective than propolis (p<0.05). Conclusion: Both Gluma and propolis were found to be effective desensitising agents, but the effectiveness of propolis decreased over one month. Clinical Trial Number: Clinical Trials.gov: NCT04819867. Key Words: Dentin hypersensitivity, Desensitizing agent, Gluma desensitiser, Propolis.